Popular weight-management apps: Their use and quality - Juliana Chen; Adrian Bauman; Janet Cade (Frontiers Media S.A., 2015)
Background: Commercial health and fitness applications (apps) are among one of the fastest growing categories of apps in recent years. However, the relationship between public engagement and quality of these dietary weight-management apps requires further investigation. Aim: To determine the most popular commercial dietary weight-management apps used by individuals and the associations between their popularity and quality. Methods: An online survey was administered to university staff and students 18 years or over. This survey included exploration of individuals' tracking of health behaviours and use of health and fitness apps. In addition, popular commercial dietary weight-loss apps (n=28) were identified from the top-200 rated free and paid 'health and fitness' apps in the Australian Apple App and Google Play stores (n=800) and scored against quality assessment criteria - encompassing components such as accountability, scientific coverage and accuracy, technology-enhanced features, usability and incorporation of behaviour change techniques. Linear regression analysis was used to determine the relationship between the rankings of the apps as per the App stores (i.e. popularity) versus the quality assessment score. Results: From the 101 completed surveys, the majority of individuals tracked weight, diet or exercise routines (93%) and did so predominantly through an app (78%). Current app users (n=85) had installed on average 3.1 (SD=1.9) health and fitness apps on their phones. The most common combination of health topics addressed by apps were physical activity and nutrition. The three most frequently reported dietary weight-loss apps were Calorie Counter by MyFitnessPal Inc. (n=47; 55%); Calorie Counter & Diet Tracker by Calorie Count (n=13; 15%); and Easy Diet Diary by Xyris Software (n=6; 7%). When evaluated against quality assessment criteria, these apps scored 54.5, 54.5 and 63 out of 100 respectively, compared to the mean overall score across all 28 popular apps of 47.3 (SD=13.9). Regression analysis indicated that those commercial weight-loss apps rated more popular in the app store were associated with a higher total quality assessment score (R2=0.375; P=0.001). Conclusions: While greater popularity of apps was associated with higher quality, the overall quality of commercial dietary weight-management apps remains suboptimal. Popular weight-management apps are useful for self-monitoring, however are lacking in the recognised behavioural change techniques that may facilitate changes in health behaviours. With the majority of these apps designed for self-directed management, strategies to improve the rigour of these apps are warranted and commercial app developers could benefit from collaboration with behavioural researchers.